The Strategy of Marketing Communication in Tourism Industry through One Village One Product Approach in West Java Province - Koswara, Iwan; Erlandia, Dedi Rumawan; Truline, Putri (International Journal of Psychosocial Rehabilitation, 2019)
The tourism industry is not only the construction of tourism infrastructure and facilities, but also how the government, the community, as well as interested parties, are involved in marketing tourist destinations. Related to that, the role of marketing communication cannot be ignored, and one of the steps in the development of the tourism sector is by communicating tourism industry marketing through a one village one product (Ovop) approach. The purpose of this study is to find out; 1. Implementation of marketing communication strategies through one village one product. 2. Steps of the Regional and Provincial governments on the marketing strategy of the tourism industry marketing one village one product. The research method used is a qualitative exploratory method, with data collection techniques through observation, interviews, focus on group discussion, source triangulation, and literature studies. The results of the study show that each district / city in West Java in carrying out marketing communications in the tourism industry, one village one product, relies on the strength and potential of each region, while the steps of the Regional and Provincial governments act as regulators and facilitators. Conclusion Ovop's superior tourism products are not only in the form of tangible products, but also in the form of intangible products, such as cultural products, regional special arts, and natural charm. Recommendation; It is necessary to make a marketing communication model for the tourism industry one village one product district / city and an integrated model between districts / cities and West Java Province.